Gender Differences in The Adoption of Mobile Banking: Review of Using TAM on Banking Customers - Sugiarto, Agung (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2016)
Mobile banking as a manifestation of the use of technology in the banking sector, has a very massive deployment level. This study focuses on the use of mobile banking technology as one of the products of information technology in the banking field. Gender differences of mobile banking users empirically shown to be affected by several factors that can be identified through modeling framework technology acceptance model (TAM), including: perceived usefulness and perceived ease of use.